2018
DOI: 10.1016/j.fertnstert.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Same-day confirmation of intrauterine pregnancy failure in women with first- and early second-trimester bleeding

Abstract: Higher concentrations of AFP in vaginal blood than in maternal serum may indicate the presence of dissolved fetal tissue (i.e., confirming a failed pregnancy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…They got a 100% sensitivity along with 87% specificity, along with AFP ratio in blood to serum showing significant diagnostic characteristics with a ratio of <=4.3 consistent with threatened abortion and that >13.4 with a failed IUP. Thus, they concluded these vaginal blood AFP could act as a novel biomarker for early pregnancy failure, since it can be obtained early and give immediate results [6].…”
Section: Vaginal Bleeding Is a Common Presentation In Early Spontaneous Abortionmentioning
confidence: 97%
See 2 more Smart Citations
“…They got a 100% sensitivity along with 87% specificity, along with AFP ratio in blood to serum showing significant diagnostic characteristics with a ratio of <=4.3 consistent with threatened abortion and that >13.4 with a failed IUP. Thus, they concluded these vaginal blood AFP could act as a novel biomarker for early pregnancy failure, since it can be obtained early and give immediate results [6].…”
Section: Vaginal Bleeding Is a Common Presentation In Early Spontaneous Abortionmentioning
confidence: 97%
“…In fetal serum AFP is>=1000 times higher than the maternal serum [5]. Thus Mor [6] hypothesized if AFP concentration in vaginal blood which contains dissolved fetus tissue is higher than AFP concentrations in maternal serum. Thus, they tried to find if relatively high AFP concentrations in early 1st trimester or early second trimester vaginal blood will confirm the presence of an IUP which has failed i.e.…”
Section: Vaginal Bleeding Is a Common Presentation In Early Spontaneous Abortionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, high AFP concentrations in the vaginal blood are suggestive of the passage of embryonic or fetal tissue and, hence, miscarriage. 7,8 A second study demonstrated the successful same-day diagnosis of miscarriage by sampling blood collected on hygienic pads and the quantitative measurements of AFP using an automated laboratory analyzer. 8 The current study was designed to offer a simple diagnostic alternative that does not require the use of an automated laboratory analyzer.…”
Section: Objectivementioning
confidence: 99%
“…This bedside test is based on prior research that has already validated the use of alpha-fetoprotein (AFP) to diagnose miscarriage. 7 The initial proof of concept was based on the quantification of AFP in vaginal blood and in maternal serum. In a pregnant individual at any gestational age, the AFP concentration is at least 1,000 times higher in the fetal serum than in the maternal serum.…”
mentioning
confidence: 99%